Anticancer and antibacterial activities of the isolated compounds from Solanum spirale Roxb. leaves - Keawsa-Ard S. (2014)
The isolations of active anticancer compounds from Solanum spirale Roxb., collected from Phayao Province, Thailand are rarely reported. The anticancer activities of hexane and methanol extracts of the leaves were investigated. The chloroform extract possessed anticancer activities against KB-Oral cavity cancer, MCF-7 breast cancer cell and NCI-H187-Small cell lung cancer with the IC 50 values of 42.73, 17.90, and 36.74 μg/ mL, respectively. But the hexane extract did not inhibit significant anticancer activity against three cancer cell lines. Lupeol, protocatechuic acid and trans-cinnamic acid have been isolated from the chloroform extract of this medicinal plants. Their structures were characterized on the basis of spectroscopic analysis. The anticancer activities of the isolated compounds were also evaluated in vitro against three cancer cell lines. Only lupeol compound inhibited significant anticancer activity against KB-Oral cavity cancer with the IC 50- value of 26.73 μg/mL, whereas protocatechuic acid and trans-cinnamic acid did not exhibit anticancer activity. The hexane, chloroform extracts and the isolated compounds did not show cytotoxic activity against the African green monkey kidney cell line. The hexane and chloroform extracts also inhibited antibacterial activity against Escherichia coli and Staphylococcus aureus with the MIC values were in the range between 375-1500 μg/mL. All isolated compounds showed equal antibacterial activity against E. coli with the MIC of 250 μg/mL, and trans-cinnamic acid showed better antibacterial activity against S. aureus with the MIC of 250 μg/mL than lupeol and protocatechuic acid. This is the first report decribes the isolation and structure elucidation of lupeol, protocatechuic acid and trans-cinnamic acid together with their anticancer, cytotoxic and antibacterial activities from this medicinal plant.